2002
DOI: 10.1002/icd.256
|View full text |Cite
|
Sign up to set email alerts
|

Is this still called a dog? 18‐month‐olds' generalization of familiar labels to unusual objects

Abstract: In two experiments the flexibility of 18-month-olds' extension of familiar object labels was investigated using the intermodal preferential looking paradigm. The first experiment tested whether infants consider intact and incomplete objects as equally acceptable referents for familiar labels. Infants looked equally long at the intact and incomplete objects whether or not a label was presented. In the second experiment, infants were requested to find the referent of a target word among an incomplete target and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
(34 reference statements)
2
9
0
Order By: Relevance
“…This also fits well with previous research on typicality effects and naming in children (e.g. Meints et al 1999, 2002, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This also fits well with previous research on typicality effects and naming in children (e.g. Meints et al 1999, 2002, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, when considering what makes something more or less ‘typical’ participants were introduced to the typicality rating task by being asked to think about a ‘true green’ as compared with a ‘brownish green’ or a ‘yellow green’. Similar instructions have been used successfully in previous studies (Meints et al 1999, 2002, 2008). All participants received the same instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as we know that infants around 12 months can already understand a range of words, for example, proper nouns, nouns, and socio‐pragmatic words (e.g., Schafer, ; Syrnyk, ), there must be an earlier point in time when we can observe the onset of their word learning abilities. Studies with 12‐ and 15‐month‐old children have shown that they can match nouns and prepositions to previously unseen, typical exemplars, but they cannot extend these words to less typical (e.g., Meints, Plunkett, & Harris, ; Meints, Plunkett, Harris, & Dimmock, ; Poulin‐Dubois & Sissons, ; Southgate & Meints, ) or broken exemplars (Meints & Jones, ) as children and adults can. Thus, young infants’ word comprehension is not just lacking in size, but also lacking in maturity when compared with older children and adults.…”
Section: Introductionmentioning
confidence: 99%